2015
DOI: 10.1249/jes.0000000000000058
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maternal Exercise during Pregnancy on Offspring Chronic Disease Susceptibility

Abstract: Maternal behaviors during pregnancy have been reported to impact offspring health in adulthood. In this review we explore the novel hypothesis that exercise during pregnancy can protect against chronic disease susceptibility in offspring. To date research has demonstrated that improvements in metabolic outcomes, cardiovascular risk, and cancer can occur in response to maternal exercise during pregnancy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 35 publications
1
41
0
1
Order By: Relevance
“…31 Table 1 summarizes the recent animal studies, and provides further details on sex differences and variation observed in lean (control) v. obese exercised dams, where appropriate. In pigs, maternal exercise during pregnancy results in enhanced endothelium-dependent vaso-relaxation response in the thoracic aorta of newborn female offspring.…”
Section: Maternal Exercise and Offspring Metabolic Phenotypesmentioning
confidence: 99%
“…31 Table 1 summarizes the recent animal studies, and provides further details on sex differences and variation observed in lean (control) v. obese exercised dams, where appropriate. In pigs, maternal exercise during pregnancy results in enhanced endothelium-dependent vaso-relaxation response in the thoracic aorta of newborn female offspring.…”
Section: Maternal Exercise and Offspring Metabolic Phenotypesmentioning
confidence: 99%
“…Regular exercise even in the 3rd trimester neither leads to an increased rate of premature delivery nor to increased hospitalisation [8,10]. Moreover, mostly on the basis of preclinical data, positive effects on the newborn in terms of longterm risk of chronic metabolic, cardiovascular and oncological diseases are discussed [11]. The American College of Obstetricians and Gynecologists (ACOG) therefore now recommends regular, moderate intensity exercise for 30 minutes at least 3 days a week [2].…”
Section: Introductionmentioning
confidence: 99%
“…It turns out that regular physical activity can bring significant benefits to pregnant women and fetus. Maternal benefits include improving cardiovascular function, lightening weight gain in pregnancy (Melzer et al 2010), mitigating musculoskeletal discomfort, reducing incidence of muscle spasms and lower limb edema, reducing risk of hypertension-related complications (Dempsey et al 2004;Blaize et al 2015). Fetal benefits include reducing fat content, improving stress tolerance and promoting nerve development (Harrod et al 2014;Marques et al 2015).…”
Section: Intervention Of Physical Activity On the Progression Of Gestmentioning
confidence: 99%